The Relation Between Minimum Wages and Poverty in Indonesia: An Islamic Perspective - Ahmad Syarif; Wahyu Hadi Wibowo (Global Review of Islamic Economics and Business, 2017)
This study is part of Islamic economics research that aims to determine the relationship between the minimum wage and poverty rate in Indonesia, especially case studies in West Java, Central Java, East Java, Special Region of Yogyakarta, and Banten during the period 2007-2013. In addition to the primary independent variable, there are six control variables are used, the level of education, the GDP per capita, unemployment rate, inflation rate, average wages and economic growth. The analysis technique used in this study are Arellano Bond Dynamic GMM (Generalized Method of Moment). The results of this study found that the minimum wage is not a significant effect on poverty levels in 2007-2013, especially in the districts/cities in West Java, Central Java, East Java, Special Region of Yogyakarta and Banten. Based on the explanation above, it can be concluded that government has responsibilities and sufficient role to reduce poverty through minimum wage standardization, the state also has responsibilities to create social security, both for those who are unable to work, informal workers and vulnerable workers, so that the level of wages (income) they can meet any basic needs according to Ibn Hazm include food, clothing, health, education and housing.